Strategic role of financial intelligence in sustainable business growth and profitability: An entrepreneurial perspective - Azuka, Ugbah Andrew; Ugeoritsete, EYIDE Michael; Jebolise, CHUKWUKA, Ernest; Onebi, Prevail Orhumurigho; Solomon, Egbule A.C (Edelweiss Applied Science and Technology, 2025)
This study is an empirical investigation into the role of financial intelligence on sustainable business growth and profitability. Finance is the life of every business and if intelligence is not applied in the management of business finance, it will lead to the pack-up of many start-ups. The study seeks to ascertain the exact role played by financial intelligence in sustainable business growth and profitability. The Study adopted a cross sectional survey research design in studying some Manufacturing Firms in Delta State which were accessible as population of study. This study empirically proved that there is a significant connection between Financial Intelligence and Sustainable Business Growth as well as a very significant connection between financial intelligence and profitability of Manufacturing firms studied and all businesses from the study reviews. These findings indicate that financial intelligence is a necessary skill or ability for manufacturing firms to be profitable and for businesses to grow sustainably. This study concludes empirically by demonstrating that financial intelligence is crucial for all entrepreneurs and business executives to have because it equips them with the knowledge and skills necessary to manage financial risks, make prudent financial decisions, and ensure long-term profitability. As the digital era advances, the importance of financial intelligence will only increase. This study also empirically proved that any start-up without financial intelligence will soon pack-up.